1995
DOI: 10.1073/pnas.92.3.925
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroanatomy of antisaccade eye movements investigated with positron emission tomography.

Abstract: Increasing interest in the role of the frontal lobe in relation to psychiatric and neurologic disorders has popularized tests of frontal function. One of these is the antisaccade task, in which both frontal lobe patients and schizophrenics are impaired despite normal performance on (pro)saccadic tasks. We used positron emission tomography to examine the cerebral blood flow changes associated with the performance of antisaccades in normal individuals. We found that the areas of the brain that were more active d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
148
3
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(174 citation statements)
references
References 32 publications
19
148
3
4
Order By: Relevance
“…Curtis and D'Esposito (2003) showed that an area near the SMA (pre-SMA) and the SEF, but not the DLPFC, is maximally active prior to the generation of an antisaccade and therefore 'prepares' other regions so that a reflex pro-saccade is less likely when the target appears. Other imaging studies have also failed to find activation in DLPFC in relation to antisaccade performance (O'Driscoll et al 1995;Raemaekers et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curtis and D'Esposito (2003) showed that an area near the SMA (pre-SMA) and the SEF, but not the DLPFC, is maximally active prior to the generation of an antisaccade and therefore 'prepares' other regions so that a reflex pro-saccade is less likely when the target appears. Other imaging studies have also failed to find activation in DLPFC in relation to antisaccade performance (O'Driscoll et al 1995;Raemaekers et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Rosano et al 2002;Petit & Haxby, 1999) and antisaccade performance (e.g. Curtis & D'Esposito, 2003;O'Driscoll et al 1995) in healthy controls do not report significant laterality effects for SEF and FEF oculomotor areas. One speculative interpretation is that our findings reflect neural immaturity in first-episode schizophrenia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine might be expected to interfere with antisaccade performance, because this type of eye movement partially depends upon intact function of prefrontal cortex (Funahashi et al 1993) and the frontal eye fields (O'Driscoll et al 1995), where NMDA receptors are functionally important (Verma and Moghaddam 1996). Brier et al (1997) have demonstrated that ketamine causes prefrontal metabolic changes that are correlated with schizophrenia-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The functional anatomy of the oculomotor system has been investigated extensively with a variety of oculomotor tasks, including voluntary, visually guided, memory-guided, and conditional saccades (29)(30)(31)(32)(33). Fig.…”
Section: Functional Anatomy Of Visual Orienting In the Human Brainmentioning
confidence: 99%